Business powers and agrarian conflicts. Conceptual notes from the approach of power resources in case studies: Moratorium Law on Transgenics (2011) and the conflict of the agrarian strike of 2020 - Armas Gonzales, Marcelo Axel (2022)
Research on business elites and economic power has notable findings in the social sciences of Peru. However, the theoretical application of this political power has not been used, especially in contexts of agrarian conflicts. The aim proposed in this theoretical essay, focused on the power resources approach, is to improve the theoretical description and explain in detail the theory of business power, its instrumental and structural mechanisms, and the strategic application of power resources. Thereby, fundamental questions about the power of business organized in unions in state institutions and conflicts that develop against other groups are addressed. To achieve this objective, two Peruvian cases are compared: the approval of the Transgenic Moratorium Law (2011) and the conflict of the agrarian strike of 2020, through the findings of previous investigations and journalistic notes regarding “business power”. Finally, this essay provides some conceptual scope and proposes to continue the research on “business power” from the resource approach so that social conflicts and the Peruvian State can be understood in a more complex way.